Effect of stress by shading on sea lavender (Limonium sp. cv. Bluestream) plants yield - Casierra-Posada, Fánor; Moreno, Deivy L. (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2011)
Under natural conditions, the environmental light of plants varies spatially and temporally in terms of quality, quantity and duration. Reduction in light quantity affects numerous aspects of plant development. Many of these effects are related to the reduction in photosynthesis and consequential changes in sugar availability. The most studied responses are those of the induction of flowering and the elongation of stems and petioles. The effect of shading prior to cut of flowers in sea lavender plants cv. Blue stream on number of leaves and harvested flowers, the leaf specific weight and the flower stem length were evaluated. Plants grew under greenhouse conditions in Guasca (Colombia). For shading, black nets of 47 and 80% light reduction 1.5 m over plants were deployed. Control plants grew without a net over. Results showed reduction by all evaluated parameters through nets in comparison to control plants, but the stem length was more negatively influenced by shading. Flower stems were 36.5 and 49.0% shorter in comparison to those harvested in control plants under nets of 47 and 80% of light reduction, respectively, affecting strongly the flower quality for exportation. Results suggested high sensibility of sea lavender plants for light reduction.